Jeca Tatu, un héros brésilien. Genèse, évolution et déplacements du personnage du caipira - Teresa Cristina Duarte-Simões (Caravelle)
The comic figure of the paulista pesant appeared for the first time in the scene in the Martins Pena’s Comédias, in the middle of the 19th century. Nevertheless, it’s the character named Jeca Tatu, created by Monteiro Lobato in 1914 who truly fixed the image of the São Paulo’s state caipira. This character will be even more popular at the end of the fifties, when it was transposed to the cinema by Amácio Mazzaropi. In spite of the years, the caipira Jeca Tatu is still very much alive in Brazilian culture. In 2006, a tribute was paid to him through the film Tapete Vermelho.